COVID-19: Lockdown and its impact on medical students: A cross sectional study from a medical school in Mauritius - Banerjee, Indrajit; Robinson, Jared; Mohabeer, Poornasha; Kashyap, Abhishek; Shukla, Ananya; Sathian, Brijesh (Nepal Journal of Epidemiology, 2021)
Background: The objectives of the study were to identify the psychological impact of lockdown on medical students due to COVID-19 and to discover the educational perplexities being faced by these students during the lockdown due to COVID-19. Methods: A cross-sectional study was conducted at Sir Seewoosagur Ramgoolam Medical College (SSRMC), Mauritius. Questions were designed after extensive review of the literature, so that they were relevant to meet the objectives of the study. Results: Out of 700 undergraduate medical students, 663 students participated in the study, this equates to a substantial response rate of 95%. Due to the pandemic 348 (52.5 %) of the students were stationed in their hometown and the remaining 315 (47.5 %) were stationed in Mauritius. 464(70%) of the students suffered from the psychological impact of lockdown whereas 634(95.6%) of the students suffered from the educational impact of lockdown. Mauritian students suffered from a greater educational impact aOR4.236[1.606-11.173]. Psychological impact aOR 1.280 [0.917-1.789] and educational impact aOR 2.464 [1.076-5.647] was found more in students those who were at their hometown. Conclusion: Lockdown triggered both educational and psychological impact on medical students. On a psychological basis it was proven that the lockdown induced a feeling of guilt and had subsequent psychological impacts in certain students. The COVID-19 situation was simultaneously indicated to be a motivator in the majority of students; however, juxtaposed to this was the fact that various students felt as if they could not study at the same level that they are accustomed to due to the uncertainty of the situation.